Governing the global fisheries commons - Paniagua, Pablo; Rayamajhee, Veeshan (Marine policy, 2024)
Despite significant advances in understanding the biophysical and institutional causes of overfishing, we have yet to make progress in addressing the depletion of our global fisheries stock. Investigations of potential solutions tend to be too broad (mischaracterizing global fisheries as a singular commons problem to be addressed at the supranational level) or too narrow (focusing on improving management of small fisheries at the micro level). This article attempts to bridge the gap between our scientific understanding of our collective dilemmas and their pragmatic solutions. Building on insights from Nobel laureate Elinor Ostrom, we frame the depletion of global fisheries as a nested set of diverse and interconnected collective action problems organized at different horizontal and vertical levels, where decisions and actions of one jurisdictional unit reinforce and amplify problems (and solutions) for other units. We examine features of the global fisheries system, such as nonstationarity, nestedness, and prohibitive transaction costs. Then, we explore some potential solutions. The success of our conservation goals depends on our ability to craft institutional rules at the lower levels that are adaptive to local conditions, address incentive misalignment issues, and allow for the transfer of positive externalities to adjacent and higher levels.